(untitled) - Damrosch, David (New York, 2009)
The Longman Anthology of British LIterature was the first collection to pay sustained attention to the contexts within which literature is produced, even as it broadened the scope of that literature to embrace the full cultural diversity of the British Isles
Keywords: English literature,Great Britain,Văn học Anh,Anh Quốc; Civilization,Nền văn minh; 20th century,20th century,Thế kỷ 20,Thế kỷ 20